World Bank Group Engagement with Morocco 2011–21 : Approach Paper - Independent Evaluation Group (Washington, DC : World Bank, 2022)
This Country Program Evaluation aims to assess the World Bank Group’s contribution to Morocco’s development trajectory over the past decade (fiscal years 2011–21) and is timed to inform the next Country Partnership Framework and future Bank Group engagements in the country. The Country Program Evaluation will use a range of methods to assess how the Bank Group has supported Morocco’s efforts to tackle major constraints to achieving its objective of reaching upper-middle-income-country status. The evaluation will focus on three outcome areas: (i) fostering private sector–led growth that absorbs a growing labor force; (ii) strengthening inclusive human capital formation and addressing the obstacles to women and youth labor force participation; and (iii) reducing climate risks and natural resource depletion and addressing their combined effects on the most vulnerable people, especially in rural areas.